2016
DOI: 10.1097/mpa.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Serum Autoantibodies for Differential Diagnosis of Autoimmune Pancreatitis and Pancreatic Ductal Adenocarcinoma

Abstract: The novel panel of AIP autoantibodies is promising to supplement the predictive tests for AIP of the currently known autoantigens and represent a basis for a combined blood test to differentiate AIP from PDAC in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Some of these antibodies are organ-specific mainly against antigens from the pancreatic ducts and acini [28,30], whereas others are not organ-specific and directed against nuclear antigen (ANA). Recently, additional autoantibodies have been identified against pancreatic enzyme precursors in AIP patients [7]. The study also reported different expression of anti-pancreatic lipase and anti-transaldolase in the two AIP-subtypes.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Some of these antibodies are organ-specific mainly against antigens from the pancreatic ducts and acini [28,30], whereas others are not organ-specific and directed against nuclear antigen (ANA). Recently, additional autoantibodies have been identified against pancreatic enzyme precursors in AIP patients [7]. The study also reported different expression of anti-pancreatic lipase and anti-transaldolase in the two AIP-subtypes.…”
Section: Discussionmentioning
confidence: 65%
“…Microarrays assembled of thousands of different proteins have been already reported and used to identify tumour associated autoantibodies in the context of colorectal cancer [25], bladder cancer [26], ovarian cancer, and pancreatic cancer [8,27]. Furthermore, several studies described elevated autoantibody concentrations in sera of patients with AIP including anti-lactoferrin [28,29], anti-carbonic anhydrase II, anti-carbonic anhydrase IV, anti-pancreas secretory trypsin inhibitor, anti-anionic and cationic trypsinogens, anti-amylase-1, anti-heat shock protein 10 and anti-plasminogen-binding protein peptide autoantibodies [7,18,30]. However, their performance as diagnostic markers is still under debate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying a multiplex ELISA for IL-1β, IL-7, and G-CSF on patients’ serum would also allow AIP-2 to be distinguished from PDAC. Combining them with the recently identified gelatinases A and B and apolipoproteins Apo-AI and Apo-AII as discriminatory parameters [5052] in a multiplex format, this could form the basis for a clinically applicable blood test, allowing reliable distinction between AIP and PDAC. This test would warrant immune-suppressive therapy without surgery for AIP patients and immediate surgical and chemotherapeutical treatment of PDAC patients.…”
Section: Discussionmentioning
confidence: 99%